Functional Characterization of PM6/13, a β3-specific (GPIIIa/CD61) Monoclonal Antibody that Shows Preferential Inhibition of Fibrinogen Binding over Fibronectin Binding to Activated Human Platelets - Patel, Yatin; Rahman, Salman; Siddiqua, Ashia; Wilkinson, Michael J.; Kakkar, Vijay V.; Authi, Kalwant S. (Thrombosis and Haemostasis, 1998)
We report the characterization of a monoclonal antibody (MAb) PM6/13 which recognises glycoprotein IIIa (GPIIIa) on platelet membranes and in functional studies inhibits platelet aggregation induced by all agonists examined. In platelet-rich plasma, inhibition of aggregation induced by ADP or low concentrations of collagen was accompanied by inhibition of 5-hydroxytryptamine secretion. EC50 values were 10 and 9 [H9262]g/ml antibody against ADP and collagen induced responses respectively. In washed platelets treated with the cyclooxygenase inhibitor, indomethacin, PM6/13 inhibited platelet aggregation induced by thrombin (0.2 U/ml), collagen (10 [H9262]g/ml) and U46619 (3 [H9262]M) with EC50 = 4, 8 and 4 [H9262]g/ml respectively, without affecting [14C]5-hydroxytryptamine secretion or [3H]arachidonate release in appropriately labelled cells. Studies in Fura 2-labelled platelets revealed that elevation of intracellular calcium by ADP, thrombin or U46619 was unaffected by PM6/13 suggesting that the epitope recognised by the antibody did not influence Ca2+ regulation. In agreement with the results from the platelet aggregation studies, PM6/13 was found to potently inhibit binding of 125I-fibrinogen to ADP activated platelets. Binding of this ligand was also inhibited by two other MAbs tested, namely SZ-21 (also to GPIIIa) and PM6/248 (to the GPIIb-IIIa complex). However when tested against binding of 125I-fibronectin to thrombin stimulated platelets, PM6/13 was ineffective in contrast with SZ-21 and PM6/248, that were both potent inhibitors. This suggested that the epitopes recognised by PM6/13 and SZ-21 on GPIIIa were distinct. Studies employing proteolytic dissection of 125I-labelled GPIIIa by trypsin followed by immunoprecipitation with PM6/13 and analysis by SDS-PAGE, revealed the presence of four fragments at 70, 55, 30 and 28 kDa. PM6/13 did not recognize any protein bands on Western blots performed under reducing conditions. However Western blotting analysis with PM6/13 under non-reducing conditions revealed strong detection of the parent GP IIIa molecule, of trypsin treated samples revealed recognition of an 80 kDa fragment at 1 min, faint recognition of a 60 kDa fragment at 60 min and no recognition of any product at 18 h treatment. Under similar conditions, SZ-21 recognized fragments at 80, 75 and 55 kDa with the 55kDa species persisting even after 18 h trypsin treatment. These studies confirm the epitopes recognised by PM6/13 and SZ-21 to be distinct and that PM6/13 represents a useful tool to differentiate the characteristics of fibrinogen and fibronectin binding to the GPIIb-IIIa complex on activated platelets.